The Influence of Adolescent health-related Behaviors on Degenerative Low Back Pain Hospitalizations and Surgeries in Adulthood : A Longitudinal Study - Vaajala, Matias; Teuho, Alisa; Liukkonen, Rasmus; Ponkilainen, Ville; Rimpelä, Arja; Koivusilta, Leena K.; Mattila, Ville M. (Lippincott Williams & Wilkins, 2025)
Objective: This study aims to investigate the influence of adolescent health-related behaviors (physical activity, high BMI, drunkenness, smoking), self-reported chronic disease, and low socioeconomic status (SES) on the development of low back pain requiring hospitalization or surgery.
Summary of background data: The baseline data were surveys gathered biennially in 1981-1997 (the Adolescent Health and Lifestyle Survey) and individually linked with outcome data, degenerative low back pain hospitalizations, and spine surgeries retrieved from the Care Register for Health Care. A total of 47 724 participants were included. Explanatory variables included physical activity, high BMI, smoking, monthly drunkenness, chronic diseases, and family SES.
Methods: A logistic regression model was used to analyze the influence of adolescent health-related behaviors (physical activity, high BMI, drunkenness, smoking), self-reported chronic disease, and low socioeconomic status (SES) on degenerative low back pain hospitalization, lumbar disc herniation (LDH) hospitalization and/or spine surgery. Covariates were selected using directed acyclic graphs (DAGs).
Results: A total of 5538 participants had degenerative low back pain hospitalizations, 2104 had LDH hospitalizations, and 913 had spinal surgery over an average of 27-years follow-up. High BMI (aOR 1.25, CI 1.12-1.38), smoking (aOR 1.53, CI 1.43-1.62), monthly drunkenness (aOR 1.17, CI 1.10-1.26), and chronic diseases (aOR 1.47, CI 1.35-1.61) in adolescence increased the odds of hospitalizations during follow-up. In addition, high BMI (aOR 1.37, CI 1.09-1.72), smoking (aOR 1.40, CI 1.21-1.61), and monthly drunkenness (aOR 1.19, CI 1.01-1.39) increased the odds of spine surgeries.
Conclusions: We found that smoking, high BMI, monthly drunkenness, chronic diseases, and low family SES in adolescence increased the likelihood of degenerative low back pain hospitalizations in adulthood. In addition, high BMI, smoking, and monthly drunkenness in adolescence increased the odds of spinal surgeries.